Perspektif Tasawuf terhadap Kematian: Death in the Perspective of Sufism - Nurul Hikmah Sofyan; Anindya Aryu Inayati (Refleksi Jurnal Filsafat dan Pemikiran Islam, 2023)
Abstract This article raises the issue of human fear of death. Fear of death will be a problem if it is excessive and does not encourage someone to prepare for death. Therefore, there is a need for study of death from sufism perspective to look again at the essence of death so that the unnatural fear of death can at least be reduced. This study uses a qualitative method with an irfani analysis technique that is adjusted to meet the need of sufism approach in this study. The result of this paper is that death is the separation of humans from what has been entrusted to humans in the world because of a moving from the world to a completely different realm. As for the destruction of body through death, it is not followed by the death of spirit. It causes spirit is created from God’s spirit, the human spirit by nature always yearns and always wants to return to where it came from. In order for the nature of spirit's longing for God to be maintained, a servant is required to always control or at least reduce worldly desires that can prevent a servant from having an inclination towards God. Keywords: Death, Body, Human Longing, Human Spirit